Osteogenic Capability of Vaterite‐Coated Nonwoven Polycaprolactone Scaffolds for In Vivo Bone Tissue Regeneration - Saveleva, Mariia S.; Ivanov, Alexey N.; Chibrikova, Julia A.; Abalymov, Anatolii A.; Surmeneva, Maria A.; Surmenev, Roman A.; Parakhonskiy, Bogdan V.; Lomova, Maria V.; Skirtach, Andre G.; Norkin, Igor A. (Macromolecular bioscience, 2021)
In current orthopedic practice, bone implants used to‐date often exhibit poor osteointegration, impaired osteogenesis, and, eventually, implant failure. Actively pursued strategies for tissue engineering could overcome these shortcomings by developing new hybrid materials with bioinspired structure and enhanced regenerative potential. In this study, the osteogenic and therapeutic potential of bioactive vaterite is investigated as a functional component of a fibrous polymeric scaffold for bone regeneration. Hybrid two‐layered polycaprolactone scaffolds coated with vaterite (PCL/CaCO3) are studied during their 28‐days implantation period in a rat femur defect. After this period, the study of tissue formation in the defected area is performed by the histological study of femur cross‐sections. Immobilization of alkaline phosphatase (ALP) into PCL/CaCO3 scaffolds accelerates new bone tissue formation and defect repair. PCL/CaCO3 and PCL/CaCO3/ALP scaffolds reveal 37.3% and 62.9% areas, respectively, filled with newly formed bone tissue in cross‐sections compared to unmineralized PCL scaffold (17.5%). Bone turnover markers are monitored on the 7th and 28th days after implantation and reveal an increase of osteocalcin level for both PCL/CaCO3 and PCL/CaCO3/ALP compared with PCL indicating the activation of osteogenesis. These findings indicate that vaterite, as an osteoconductive component of polymeric scaffolds, promotes osteogenesis, supports angiogenesis, and facilitates bone defect repair. Hybrid organic‐inorganic composites with biomimetic architecture are representing advantage materials for bone regeneration. Vaterite, which is highly‐porous calcium carbonate polymorph, serves as a new effective osteoconductive agent for fibrous polymeric scaffold. Vaterite remarkably improves osteogenesis in scaffold and facilitates its osteointegration. Porous structure of vaterite endows the scaffold with loading capacity for bioactive drugs and carrying them in implantation area.